Hydroxyproline Assay Using NaBr/NaOCl - Derek Lamport (Bio-Protocol, 2013)
Hydroxyproline (Hyp) is a major constituent of a relatively few proteins that are major structural components of the extracellular matrix and primary cell wall of animals and plants respectively. Significant amounts of the cyclic amino acids proline and hydroxyproline decrease polypeptide flexibility; thus proline/hydroxyproline-rich proteins are ideal scaffold components. Collagens typify animal tissues but extensins, arabinogalactan proteins (AGPs) and their close relatives, collectively referred to as hydroxyproline-rich glycoproteins (HRGPs), typify plants (Lamport et al., 2011). While collagens are minimally glycosylated generally via a galactosyl hydroxylysine linkage, plant HRGP glycosylation involves short neutral oligosaccharides (in extensins) or much larger acidic polysaccharide substituents (in AGPs) O-linked via the hydroxyproline hydroxyl group. Hydroxyproline assay is thus an integral part of their characterization and dominates the biochemical properties of these glycoproteins. The colourimetric assay described here quantifies free hydroxyproline (e.g. released by acid hydrolysis) based on Kivirikko and Liesmma (1959) with hypobromite as an oxidant but modified by avoiding the use of hazardous liquid bromine. A number of oxidants have been used over the years, Vogel (1961, page 395) explains the preference for hypobromite as follows: “Hypochlorites tend to react slowly with reducing agents. Hypobromites although rather unstable when prepared directly from bromine and alkali, often react more rapidly; it is therefore advantageous to produce hypobromite in situ by adding an excess of bromide to the sample of hypochlorite:” OCl- + Br- → OBr- + Cl- “By this means the relative stability of hypochlorite is combined with the more effective oxidizing properties of hypobromite.”